The God who makes himself known : the missionary heart of the book of Exodus - Blackburn, W. Ross. (Downers Grove, Ill. : Apollos, InterVarsity Press, 2012)
Countering scholarly tendencies to fragment the text due to theological problems, Ross Blackburn contends that Exodus can be read as a unified whole, and that an appreciation of this missionary theme in its canonical context is of great help in dealing with difficult issues that the books poses.
The name of the redeemer (Exod. 1:1-15:21) -- Training in the wilderness (Exod. 15:22-18:27) -- The law and the mission of God (Exod. 19-24) -- The tabernacle instructions (Exod. 25-31) -- The golden calf (Exod. 32-34) -- The tabernacle construction (Exod. 35-40).
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Missions -- Biblical teaching; God (Christianity) -- Knowableness -- Biblical teaching